Flexible phase change organogel with visualization function for human heat harvesting. (June 2023) - Zheng, Keyang; Li, Hongqiang; Xu, Junhuang; Lai, Xuejun; Chen, Zhonghua; Zeng, Xingrong
Graphical abstract: Highlights: A flexible phase change organogel (PCOG) with visualization function was prepared. The PCOG possessed high flexibility and excellent adhesion performance. The PCOG showed high latent heat of 121.7 J/g and encapsulation rate of 60.6%. The PCOG displayed visualization function for phase change process by naked eye. The generated electrical potential of the TEG adhered by the PCOG was obviously increased. Abstract: Phase change materials (PCMs) are highly promising materials in the field of energy harvesting. However, most of them lack flexibility and visualization function. Herein, a flexible phase change organogel (PCOG) was prepared via one-step in-situ polymerization reaction for the construction of three-dimensional network to "lock" n-dodecanol as PCM. The PCOG demonstrated excellent flexibility, high latent heat of 121.7 J/g and encapsulation rate of 60.6%, and also exhibited excellent cycling stability. The transmittance of the PCOG increased from 15% to 85% with the phase change process, displaying the visualization function. Furthermore, the PCOG also showed superior adhesion performance on different substrates. The generated electrical potential of a commercial thermoelectric generator adhered by the PCOG was 3 times higher than that without PCOG using human body as thermal source. Our findings provided a new strategy to prepare functional composite PCMs and the PCOG showed great potential in energy harvesting, storage and utilization.